On the effects of soil properties on leak noise propagation in plastic water distribution pipes - Brennan, M. J. [UNESP]; Karimi, M.; Muggleton, J. M.; Almeida, F. C.L. [UNESP]; Kroll de Lima, F. [UNESP]; Ayala, P. C. [UNESP]; Obata, D. [UNESP]; Paschoalini, A. T. [UNESP]; Kessissoglou, N. (Elsevier, 2018)
In many countries, leaks are located in water distribution pipes by using the cross-correlation of pipe vibration measured either side of a suspected leak. However, in modern plastic pipes this can be problematic due to strong coupling between the water, the pipe and the soil, affecting the propagation of leak noise within the pipe. This paper concerns an analytical, numerical and experimental investigation into the way in which soil properties influence leak noise propagation in buried plastic water pipes. The analytical model allows a detailed investigation into the physical effects of the soil on leak noise (wave) propagation in the pipe, in particular on the wave-speed and wave attenuation. Results highlight that, in addition to the pipe hoop stiffness, the shear stiffness of the soil can have a significant effect on the wave-speed in the pipe. Experimental measurements were conducted at two different sites - one in the UK and the other in Brazil. In the UK system, both dilatational and shear waves in the soil propagate away from the pipe, resulting in large wave attenuation in the pipe. However, in the Brazilian system, only shear waves propagate resulting in smaller wave attenuation in the pipe.
Keywords: Pipe vibro-acoustics; Water leak detection; Wave propagation